If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -11 = 2(x + -8) Combine like terms: 15 + -11 = 4 4 = 2(x + -8) Reorder the terms: 4 = 2(-8 + x) 4 = (-8 * 2 + x * 2) 4 = (-16 + 2x) Solving 4 = -16 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 4 + -2x = -16 + 2x + -2x Combine like terms: 2x + -2x = 0 4 + -2x = -16 + 0 4 + -2x = -16 Add '-4' to each side of the equation. 4 + -4 + -2x = -16 + -4 Combine like terms: 4 + -4 = 0 0 + -2x = -16 + -4 -2x = -16 + -4 Combine like terms: -16 + -4 = -20 -2x = -20 Divide each side by '-2'. x = 10 Simplifying x = 10
| 6(y-1)=5y+4 | | 20x+4=6x+4 | | -4(y+1)=0 | | 20x+4=8x+18 | | 4x^2-12x+9=equation | | 2/3x-5/3x | | 4(y+3)=2y+20 | | 3(6)-3(-4)+10(-2)=10 | | 30=5d-3d | | -2.24n=-12.168 | | x-12=x/10 | | 7x-1=8x+2 | | X-3-3x=3(1+x) | | y^4+12y^2+36=0 | | n/-15=5.3 | | 5(2x+6)=55 | | 1.6=4y+20.4 | | 2cos(x)-3x=0 | | 3x+4=9.5 | | n/14.3=-5 | | -0.166666666667= | | 0.5(y+8)=2(y-1) | | 7+8q=7q | | H=-16t^2+24t+40 | | -2x-1=2x+15 | | n/-12.168=-2 | | z+iz+1=0 | | 12(n+8)=132 | | 10(x+3)-9x-4=x-5+3 | | 4x-15=7x-60 | | (7x+15)=8x | | 2(x-4)=35 |